X chromosomes and autosomes evolve at similar rates in Drosophila: No evidence for faster-X protein evolution - Thornton, Kevin; Bachtrog, Doris; Andolfatto, Peter

(untitled) (Genome Research, 2006)
Recent data from Drosophila suggest that a substantial fraction of amino acid substitutions observed between species are beneficial. If these beneficial mutations are on average partially recessive, then the rate of protein evolution is predicted to be faster for X-linked genes compared to autosomal genes (the “faster-X” hypothesis). We test this prediction by comparing rates of protein substitutions between orthologous genes, taking advantage of variations in chromosome fusions within the genus Drosophila. In members of the Drosophila melanogaster species group, the chromosomal arm 3L segregates as an ordinary autosome (i.e., two homologous copies in both males and females). However, in the Drosophila pseudoobscura species group, this chromosomal arm has become fused to the ancestral X chromosome and is hemizygous in males. The faster-X hypothesis predicts that protein evolution should be faster for genes on this chromosomal arm in the D. pseudoobscura lineage, relative to the D. melanogaster lineage. Here we combine new sequence data for 202 gene fragments in Drosophila miranda (in the pseudoobscura species group) with the completed genomes of D. melanogaster, D. pseudoobscura, and Drosophila yakuba to show that there are no detectable differences in rates of amino acid evolution for orthologous X-linked and autosomal genes. Our results imply that the contribution of the faster-X (if any) to the large-X effect on reproductive isolation in Drosophila is not due to a generally faster rate of protein evolution. The lack of a detectable faster-X effect in these species suggests either that beneficial amino acids are not partially recessive on average, or that adaptive evolution does not often use newly arising amino acid mutations.